Trophic and Guild Interactions in Biological Control - Brodeur, Jacques.; Brodeur, Jacques.; Boivin, Guy.; Boivin, Guy. (Progress in Biological Control, 2006)
This volume explores modern concepts of trophic and guild interactions among natural enemies in natural and agricultural ecosystems - a field that has become a hot topic in ecology and biological control over the past decade. Internationally recognized scientists have combined their expertise and passion to examine how species interactions between biological control agents, such as competition, predation, parasitism, disease infection, mutualism, and omnivory affect arthropod population dynamics and the outcome of biological control. The common approach is the use of ecological theory to better interpret the prevalence, nature and outcome of trophic and guild interactions and, from a more applied perspective, to gain a comprehensive understanding of how and when to use biological control.